2015
DOI: 10.1038/ncomms10068
|View full text |Cite
|
Sign up to set email alerts
|

PTEN deficiency reprogrammes human neural stem cells towards a glioblastoma stem cell-like phenotype

Abstract: PTEN is a tumour suppressor frequently mutated in many types of cancers. Here we show that targeted disruption of PTEN leads to neoplastic transformation of human neural stem cells (NSCs), but not mesenchymal stem cells. PTEN-deficient NSCs display neoplasm-associated metabolic and gene expression profiles and generate intracranial tumours in immunodeficient mice. PTEN is localized to the nucleus in NSCs, binds to the PAX7 promoter through association with cAMP responsive element binding protein 1 (CREB)/CREB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 71 publications
(101 reference statements)
2
132
0
1
Order By: Relevance
“…Firefly luciferase activity was normalized to renilla luciferase activity for each transfected cell sample. The specific procedure was performed according to a published paper (Duan et al., 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Firefly luciferase activity was normalized to renilla luciferase activity for each transfected cell sample. The specific procedure was performed according to a published paper (Duan et al., 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Already, this approach has shown promise in other genes. Engineered human embryonic stem cell (ESC)-derived neural progenitor cells (NPCs) and neural stem cells (NSCs) have been used to study and model diffuse intrinsic pontine gliomas (DIPGs) [196] and GBM [197] respectively. Both of these studies identified novel potential drugs for brain tumors.…”
Section: Translating Lfs Ipsc Models Into Clinical Therapiesmentioning
confidence: 99%
“…Several groups have applied patient-derived iPSCs and/or engineered PSCs to phenocopy cancer features, explore disease mechanisms and screen potential therapeutic drugs [3034]. Their experience highlights the potential of human PSCs in cancer studies by overcoming limitations related to availability of patient samples or translation of results from animal models or cell lines with inappropriate genetic backgrounds.…”
Section: Modeling Disease With Pluripotent Stem Cellsmentioning
confidence: 99%
“…While GBMs are genetically very diverse, mutations in PTEN are common and correlate with increased invasion, drug resistance and tumor recurrence [41]. Duan et al engineered PTEN-deficient ESCs using a TALEN-based genome editing methodology and derived neural stem cells (NSCs) to model GBM [34]. PTEN-deficient NSCs displayed the GBM-associated gene signature and formed intracranial tumors in vivo .…”
Section: Glioblastoma Multiforme (Gbm)mentioning
confidence: 99%
See 1 more Smart Citation